Fenomena Harga Saham: Ukuran Perusahaan, Pertumbuhan Perusahaan, Pertumbuhan Penjualan, Likuiditas dan Profitabilitas pada Perusahaan Energy yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Dila Pertiwi; Mujiyati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of firm size, firm growth, sales growth, liquidity, and profitability on stock prices of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research uses a quantitative approach with multiple linear regression analysis techniques. Data were collected from the annual financial reports of six energy companies selected through purposive sampling. The results show that simultaneously the five independent variables significantly affect stock prices. Partially, firm size, sales growth, and liquidity have a significant effect, while firm growth and profitability have no significant effect. This research contributes to investors in evaluating financial factors before making investment decisions.